Molecular cloning, expression, purification and crystallization of BcsG for structural analysis in escherichia coli - Lee, Jin (2018)
Cellulose is an important component of plants and bacteria, contributing to many physiological and chemical properties. In E.coli and other Gram-Negative bacteria, a chemically modified cellulose variant, phosphoethanolamine (pEtN) cellulose, is required for extracellular matrix assembly and biofilm formation. BcsA and BcsB are 2 well-documented major genes responsible for 2 major protein subunits and required for bacterial cellulose synthase formation. Genes such as BcsG have been found to play a crucial role in cellulose synthase formation as well and yet, little is known about BcsG apart from functional studies and theorized interaction with other Bcs proteins. BcsG was cloned, expressed in Escherichia coli, purified and underwent crystallization screens, elucidating the hydrophilic properties and high expression level of BcsG and its active domain, BcsG(A). Methods to enhance BcsG crystallization via usage of a truncated BcsG(A) domain were also examined. Finally, the ubiquity and essential need of BcsG(A) in Escherichia coli was further corroborated with prior functional studies.